2022
DOI: 10.22487/j24775185.2022.v11.i2.pp72-76
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Natural Clay from Gowa Regency, South Sulawesi Province, Indonesia

Abstract: Clay is one of the essential natural minerals in human life, especially in the industrial sector, which is widely used as a raw material for ceramics fabrication, adsorbents, and photocatalysts. The characteristics of clay significantly affect the quality of the resulting material. This study will study the aspects of natural clay in Gowa Regency, South Sulawesi Province, without the leaching process and with acid leaching. Acid leaching uses 3 M HCl, previously roasted at a temperature of 600 oC. The characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
1
5
0
Order By: Relevance
“…From Table 1, it can be identified that both NC-1 and NC-2 have main component Fe, Si, and followed by Al elements. The high content of Fe is usually found in natural clay and similar with previous study (Side & Putri, 2022).…”
Section: Xrf Characterizationsupporting
confidence: 92%
See 1 more Smart Citation
“…From Table 1, it can be identified that both NC-1 and NC-2 have main component Fe, Si, and followed by Al elements. The high content of Fe is usually found in natural clay and similar with previous study (Side & Putri, 2022).…”
Section: Xrf Characterizationsupporting
confidence: 92%
“…The main component of clay in District Tanah Miring Merauke are quartz, illite, nordstrandite, hematite, and osbornite, and has high crystallinity (Darwanto et al, 2019). The main component of natural clay from Gowa, South Sulawesi are Fe2O3, Al2O3, and SiO2, while the main mineral components are quartz, kaolinite, and hematite (Side & Putri, 2022). XRD result of natural clay from Bojonegoro, East Java showed that it consists of kaolin, quartz, and feldspar minerals (Setyaningrum et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One of the provinces in Indonesia which has quite abundant mineral resources in the form of clay is South Sulawesi, particularly in Gowa Regency. Previous researchers have reported that the mineral content in the natural clay of Gowa Regency is quartz, kaolinite, hematite (Side and Putri 2022). Thus, based on the mineral constituent compounds, the Gowa district natural clay sample has a fairly high alumina silica content.…”
Section: Introductionmentioning
confidence: 94%
“…The properties of natural clay are one of the crucial factors that must be researched before using clay in this application. Clay's expanding properties are substantially influenced by the mineralogy of its component parts and its microstructure (Side & Putri, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As for the mineral content further investigated, it was found that some of the main minerals in the natural clay of Gowa Regency were quartz (SiO2), kaolinite (Al2O3•2SiO2•2H2O), and hematite (Fe2O3.H2O). In addition, it also contains several minor minerals, namely goethite (FeOOH), magnetite (Fe3O4), and anatase (TiO2) (Side & Putri, 2022). Thus, the chemical and physical properties of natural clay are highly dependent on the region and geology of origin.…”
Section: Introductionmentioning
confidence: 99%